“Herramientas tecnológicas para el aprendizaje del área de Ciencias Naturales” - Banda Checa, María Josefina (2022)
The educational system faces the use of Information and Communication Technologies (ICT) challenge to provide learners with tools and knowledge that are required in the 21st century. These resources demand the current innovation since they allow educational actors to generate changes during the educational practice. Whereby, students' learning in the Natural Sciences subject is seen as rote, receptive and mechanical aspect because teachers do not employ different technological didactic resources to transmit knowledge as well as motivates and arouse their interest to learn. This study aims at applying the GoConqr technological tool for Natural Sciences area learning to students from the "Vicente León" educational unit located in Latacunga canton, Cotopaxi province, in 2021. The interpretive paradigm was used as a methodology because it focused on analyzing the experiences with the students. Likewise, to comprehend the educational phenomena from participants' perspectives, we employed qualitative research by following its four stages: preparatory, fieldwork, analytics and computing. We also used the inductive method and the observation technique. Both of them allowed us to get collect important data from the research subjects. The findings show the validity of technological didactic resources to share contents that are mental maps and study sheets for teachers and students, these tools serve as educational support material for sixth-grade basic education students in the Natural Sciences subject. In this way, this research contributes to strengthening the teaching and learning process through the use of didactic resources based on technology. It will aid learners to improve their classroom work and learning experiences when addressing the several topics in a creative and innovative way.